Effects of high pulling speeds on mechanical properties and morphology of pultruded GFRP composite flat laminates. (1st December 2022) - Vedernikov, Alexander; Gemi, Lokman; Madenci, Emrah; Onuralp Özkılıç, Yasin; Yazman, Şakir; Gusev, Sergey; Sulimov, Artem; Bondareva, Julia; Evlashin, Stanislav; Konev, Stepan; Akhatov, Iskander; Safonov, Alexander
Abstract: The economic efficiency of pultrusion can be significantly improved by operating the process at higher pulling speeds. This experimental study analyzed the relationships between the pulling speed, morphology, and mechanical properties of pultruded glass fiber/vinyl ester resin structural composites. Four batches of 150 mm × 3.5 mm flat laminates were produced at pulling speeds of 200, 600, 1000, and 1400 mm/min. Optical and scanning electron microscopy (SEM) were used to study the morphology of the produced flat laminates. The flexural and interlaminar shear properties were determined for both 0° and 90° fiber orientations. The observed difference in the mechanical characteristics of flat laminates can be explained by the presence of bubbles, longitudinal voids, and matrix cracks and by an increase in their density and dimensions with an increase in pulling speed. This study is the first one to demonstrate the possibility of high speed pultrusion of large cross-section profiles suitable for structural application. Authors were able to achieve the pulling speed of 1000 mm/min, increasing the output by as much as 1.7 times as compared to the regular speed pultrusion, without compromising significantly the mechanical performance of produced profiles. The results of this study would be of assistance for a better understanding of high-speed pultrusion.